The Impact of Social Media Use on Mental Health Among Adolescents - Arshad Hussain; Fouzia Luqman; Hashmat Ali; Muhammad Idris; Tufail Ahmad; Nazim Shahzad (Social Science Review Archives, 2025)
The use of social media in adolescent life was evaluated for the potential impact it might have on mental health through aspects such as depression, anxiety, and self-esteem. Because many youths around the world engage actively in using social media, their psychological impacts have to be analyzed thoroughly. A cross-sectional survey design was used, in which 165 adolescents between 18 and 25 years of age were involved. The adopted questionnaire helped in assessing usage patterns of social media and mental health status, mainly discussing depression, anxiety, and self-esteem among adolescents. The results showed that heavy use of social media (over three hours a day) was significantly associated with higher levels of depression, anxiety, and lower self-esteem. A significant number of participants who spent more time on social media platforms reported emotional distress, and social comparison and managing online images were identified as key contributors. The findings of this study are in line with the existing literature, which confirms the negative impact of social media on adolescent mental health. The study calls for further research into protective factors and coping mechanisms and emphasizes the need to promote responsible social media use to safeguard youth well-being.